Weber : political writings - Weber, Max, 1864-1920; Lassman, Peter; Speirs, Ronald (Cambridge : Cambridge University Press, 1994)
Max Weber (1864-1920), generally known as a founder of modern social science, was concerned with political affairs throughout his life. The texts in this edition span his career and include his early inaugural lecture The Nation State and Economic Policy, Suffrage and Democracy in Germany, Parliament and Government in Germany under a New Political Order, Socialism, The Profession and Vocation of Politics, and an excerpt from his essay The Situation of Constitutional Democracy in Russia, as well as other shorter writings. Together they illustrate the development of his thinking on the fate of Germany and the nature of politics in the modern western state in an age of cultural 'disenchantment'. The introduction discusses the central themes of Weber's political thought, and a chronology, notes and an annotated bibliography place him in his political and intellectual context.
Title from publisher's bibliographic system (viewed on 26 Sep 2018).
Keywords: elektronické knihy; electronic books; Political science